Ethnobotanical study of medicinal plants traditionally used for osteoporosis treatments in Boumerdes region of Algeria - Maamri, Sarra; Laoufi, Razika; Dahamni, Romaïssa; Amrouni, Sarah; Lourguioui, Wahiba; Chebouti-Meziou , Nadjiba (Ethnobotany Research and Applications, 2025)
Background: Osteoporosis is a serious health problem, especially among the elderly. Characterized by progressive bone loss, it increases the risk of fractures, which contribute to significant morbidity, mortality, and healthcare costs. Many medicinal plants used in traditional medicine contain bioactive compounds with potential skeletal benefits. This study aims to identify and document the medicinal plants traditionally used to manage osteoporosis in Algeria. Methods: Ethnomedicinal data were collected through face-to-face interviews with 48 traditional herbalists in Boumerdes Province in Algeria, using semi-structured questionnaires. Information gathered included vernacular plant names, parts used, and preparation methods. The data were analyzed using quantitative ethnobotanical indices, the relative frequency of citation (RFC). Results: The study recorded that the local population uses 54 plant species from 32 botanical families. The most common families are Fabaceae (5 taxa), Lamiaceae (5 taxa), and Poaceae (5 taxa). Lepidium sativum and Eleusine coracana emerged as the most frequently cited species. Seeds were the most commonly used plant part (31%), followed by leaves (20%) and leafy stems (14%). Remedies were primarily administered orally, with powders being the most common preparation method (25.37%), followed by decoctions (19.4%) and infusions (17.91%). Additionally, the literature shows that several experimental studies confirm the role of 48 plants from this list in treating osteoporosis. Conclusions: This study provides a comprehensive ethnobotanical record of traditional treatments for osteoporosis in Boumerdes and offers a foundation for future interdisciplinary research involving ethnobotany, pharmacology, and clinical sciences. The findings highlight the potential of several plant species for phytochemical and pharmacological investigation, with the prospect of developing novel natural therapies for bone health with fewer adverse effects. Keywords: Ethnobotany, Osteoporosis; Medicinal plant, Relative frequency of citation, Boumerdes City, Algeria